Measuring Performance of Food Supply Chain in Libyan Industrial Organizations: A Balanced Scorecard Approach - Almbsot, Fathi; ElAssal, Ahmed; Attia, ElAwady (Conference On Engineering Science and Technology, 2021)
The current paper identifies the most important Key Performance Indicators (KPIs) for measuring the food supply chain’s performance using the Balanced Scorecard (BSC). A qualitative analysis was performed in cooperation with domain experts who practise Food Supply Chain (FSC) through interviews with managers from the Libyan food industrial organizations. For each BSC perspective, a set of 20 KPIs was considered in the analysis, a total of 80 KPIs related the four perspectives. KPIs were collected through studying previous studies and researches related food supply chain. The questionnaire was prepared and distributed on (125) individuals who work in the five levels of SC; (25) individuals for each level, namely, suppliers (S), manufacturing (M), wholesalers (W) retailers (R) and customer (C). The questionnaire was analysed, results highlighted only a shortlist of metrics (only 7, 5, 7, 4 KPIs) respectively for financial, customer, internal process, and learning & growth perspectives. Consequently, a generic BSC model was constructed that can be used for any stage of the food supply chain that includes suppliers, manufacturers, wholesalers, retailers, and customers. The proposed model was agreed upon by the industrial experts. Different performance criteria that can be measured by the proposed BSC include reliability, integration, agility, responsiveness, risk management, product safety, collaboration, assets management, cost/profit, time, and sustainability.
Keywords: Balanced Score card; Food Supply Chain; performance indicators; Performance measurement